The battle for nature lovers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Ecotourism is booming. A growing number of the world s tourist hordes now seek leisure and diversion in nature, in solidarity with local people and without snapping a twig. If you and the local ecology are their destination, is it all as benign as...